Fostering Creativity and Critical Thinking in College: A Cross-Cultural Investigation - Park, Ji Hoon; Niu, Weihua; Cheng, Li; Allen, Heavon (Frontiers in Psychology, 2021)
Enhancing creativity and critical thinking have garnered the attention of educators and researchers for decades. They have been highlighted as essential skills for the 21st century (National Education Association, 2012). One hundred and three US students (53 female, 24 male, two non-binary, 24 non-reporting) and 166 Chinese students (128 female, 30 male, one non-binary, seven non-reporting) completed an online survey. The survey includes the STEAM-related creative problem solving, Sternberg scientific reasoning tasks, psychological critical thinking exam, California critical thinking skills test, and college experience survey, as well as a demographic questionnaire. A confirmatory factor analysis (CFA) yields a two-factor model for all creativity and critical thinking measurements. Yet, the two latent factors are strongly associated with each other (r =.84). Moreover, Chinese students outperform American students in measures of critical thinking, whereas Americans outperform Chinese students in measures of creativity. Lastly, the results also demonstrate that having some college research experience (such as taking research method courses) could positively influence both US and Chinese students' creativity and critical thinking skills. Implications are discussed.